The sensory arrays of the ant, Temnothorax rugatulus. Issue 4 (July 2017) - Ramirez-Esquivel, Fiorella; Leitner, Nicole E.; Zeil, Jochen; Narendra, Ajay
Abstract: Individual differences in response thresholds to task-related stimuli may be one mechanism driving task allocation among social insect workers. These differences may arise at various stages in the nervous system. We investigate variability in the peripheral nervous system as a simple mechanism that can introduce inter-individual differences in sensory information. In this study we describe size-dependent variation of the compound eyes and the antennae in the ant Temnothorax rugatulus . Head width in T. rugatulus varies between 0.4 and 0.7 mm (2.6–3.8 mm body length). But despite this limited range of worker sizes we find sensory array variability. We find that the number of ommatidia and of some, but not all, antennal sensilla types vary with head width. The antennal array of T. rugatulus displays the full complement of sensillum types observed in other species of ants, although at much lower quantities than other, larger, studied species. In addition, we describe what we believe to be a new type of sensillum in hymenoptera that occurs on the antennae and on all body segments. T. rugatulus has apposition compound eyes with 45–76 facets per eye, depending on head width, with average lens diameters of 16.5 μm, rhabdom diameters of 5.7 μm and inter-ommatidial angles of 16.8°. The optical system of T. rugatulus ommatidia is severely under focussed, but the absolute sensitivity of the eyes is unusually high. We discuss the functional significance of these findings and the extent to which the variability of sensory arrays may correlate with task allocation. Highlights: We describe in detail the antennal and visual arrays of an important study species Temnothorax rugatulus . We present differences in the sensory systems of seemingly uniform workers. Increased sensillum numbers in larger workers may be linked to increased chemo-sensitivity. Increased facet numbers in larger workers may assist in visual foraging. We report the presence of a sensillum type (palmate sensilla) previously not described in ants.